Venous thrombosis in pancreaticobiliary tract cancer: outcome and prognostic factors. (24th February 2015) - Larsen, A. C.; Brøndum Frøkjær, J.; Wishwanath Iyer, V.; Vincents Fisker, R.; Sall, M.; Yilmaz, M. K.; Kuno Møller, B.; Kristensen, S. R.; Thorlacius‐Ussing, O.
Summary Background The differences in outcome among cancer patients with incidental vs. symptomatic venous thromboembolism (VTE) are unknown. In this study, patients with extrahepatic pancreaticobiliary tract cancer (PBC) were selected for a prospective cohort study between February 2008 and February 2011. Methods At the time of cancer diagnosis, all patients were examined for deep vein thrombosis with bilateral compression ultrasonography (biCUS). Computed tomography pulmonary angiography was also performed to diagnose pulmonary embolisms. After inclusion, the patients were followed up with clinical examinations, blood collections, and biCUS. Results A total of 121 PBC patients were enrolled. At the time of cancer diagnosis, 15 patients had experienced a VTE (12.4%, 95% confidence interval [CI] 7.1–19.6), including six symptomatic and nine incidental cases. A total of 25 first‐time VTE events were identified (20.7%; 95% CI 13.8–29.0). Patients with a VTE had reduced survival, with a median overall survival (OS) of 4.4 months (95% CI 2.2–11.5). The median OS of the patients with incidental VTE was 3.0 months (95% CI 0.1–15.0), which was not different from the median OS of the patients with symptomatic VTE (5.0 months; 95% CI 2.1–14.5). The median OS was 11.9 months (95% CI 8.1–14.7) in the PBC patients with no VTEs. Conclusion The occurrence of a VTE event in a PBC patient within the first months of the disease is associated with significantly increased mortality.